Job Enrichment: A Tool For Motivation And Retention Of Hotel Employees (PUSA Journal of Hospitality and Applied Sciences, 2020)
Background: Job enrichment is an idea developed by Frederick Herzberg. It is a job design  technique of motivating employees by adding responsibility and variety to their job. It is  a vertical expansion of the job with the aim to make the position more satisfying and add  value to the employee’s job. Job Enrichment when applied in hotels can help adding value to  employees’ jobs, cope dissatisfaction, attrition and retaining employees in the organization.  Objective: The present study extended to study the role of job enrichment in motivating  and retaining the hotel employees. Methodology: A structured questionnaire was adopted  & the study was conducted in a hotel of Delhi. Convenience sampling technique was used  and the sample size consisted of 30 hotel employees. Results: The findings of the study  showed that employees believed that job enrichment has a significant effect in increasing  motivation (76%), decreasing absenteeism (55%) and reducing turnover (43%) in hotels.  Conclusion: Human Resources department in hotels should consider implementing various  approaches of job enrichment which includes giving task variety, increasing autonomy,  feedback on regular basis in order to deal with dissatisfaction and turnover of employees.
Keywords: Job Enrichment; Motivation; Absenteeism; Turnover